Plan de negocio para la constitución de una sociedad dirigida al transporte terrestre automotor en La Loma Cesar - Camargo Padilla, Sandy Paola; Hernández Díaz, Luisa Fernanda (Universidad Antonio Nariño, 2024)
This work seeks to provide a solution to the mobility problem in the face of the lack of regulation in the provision of public transportation service in motorcycles in the town of La Loma, Cesar in the municipality of El Paso and to create a public transportation cooperative that generates employment and improve the quality of life of the community, while reducing environmental pollution and increasing transportation safety.